Evaluasi Kualitas Layanan Nasabah dengan Metode Kano, Analisis Kuadran dan Triz Studi Kasus: Bank Nagari Cabang Pembantu Universitas Bung Hatta Padang - Dewi Oktaviani; Hilma Raimona Zadry (Jurnal Optimasi Sistem Industri, 2016)
The banking industry is one of the pulse of Indonesian economic system. Bank Nagari is an industry aims to support the community’s economic development in West Sumatra. These objectives can be realized if Bank Nagari is able to face the existing challenges and problems. However, based on the preliminary studies, it was found a weakness in the bank services, such as the irreverent attitude of the tellers to the customers and long queues at certain times. Therefore, there is a need for a solution and quick actions so that Bank Nagari can improve customer satisfaction and provide excellent service to the communities. This study was conducted at Bank Nagari branch Bung Hatta University, Padang. Data is collected using questionnaire. The questionnaires were distributed to 97 respondents consisted of 24 variables and analyzed using the Kano method, quadrant analysis, and Theory of Inventive Problem Solving (TRIZ). The study proposed improvements to Bank Nagari branch Bung Hatta University, Padang. It is proposed to install a bulletin board or poster containing bank service procedures and information about bank services, to provide training to the bank employees, to focus on the frequent bank service problems and the evolution of the bank service system from traditional services to phone banking or internet banking.